Update on Essential Hypertension 2016
DOI: 10.5772/63501
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids in Blood Pressure Control and Essential Hypertension

Abstract: Hypertension is a worldwide problem that affects up to % of adults and contributes to the global burden of disability due to cardiovascular disease. Several factors influence blood pressure and participate to the development of hypertension. "mong these factors, polyunsaturated fatty acids of the omega-family omega-PUF" are effective hypotensive agents. Through their anti-inflammatory and antioxidant properties, omega-PUF" can improve cardiac hemodynamics and vascular function and potentially reduce arterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…The prescription of ω-3 PUFAs was associated with improvement of arterial stiffness parameters and this effect was not connected to changes in body mass index, heart rate and blood pressure (BP). At a recent time in a larger randomized controlled trial on healthy persons the same author showed that a high dose ω-3 fish oil consumption (6 g/day) could reduce two indirect measurements of arterial stiffness and central BP, namely aortic pulse pressure and AIxao [11,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prescription of ω-3 PUFAs was associated with improvement of arterial stiffness parameters and this effect was not connected to changes in body mass index, heart rate and blood pressure (BP). At a recent time in a larger randomized controlled trial on healthy persons the same author showed that a high dose ω-3 fish oil consumption (6 g/day) could reduce two indirect measurements of arterial stiffness and central BP, namely aortic pulse pressure and AIxao [11,7].…”
Section: Discussionmentioning
confidence: 99%
“…The inverse association between the level of circulatory ω-3 PUFAs or of its consumption and the brachial artery cross-sectional diameter has been reported by some authors. It was demonstrated that the content of ω-3 PUFAs in membrane is directly associated with the degree of vasodilatation observed after sublingual nitrate intake, that can serve as evidence of their beneficial effect on the vascular wall [7]. Ω-3 PUFA dose-dependently prevent the diabetes manifestation, decrease insulin resistance (IR), improve the sensitivity of platelets to collagen and ADP, lead to positive changes in endothelial cells migration and the coagulation parameters, enhance and inhibit smooth muscle cells proliferation [5,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and blood pressure Omega-3 PUFAs intake has shown to reduce BP especially in hypertensive patients by interacting with several mechanisms of blood pressure regulation: reduction of stroke volume and heart rate (HR); improvement of left ventricular (LV) diastolic filling; reduction of peripheral vascular resistances; improvement of endothelial-dependent and endothelial-independent vasodilation (stimulation of NO production; reduction of the asymmetric di-methyl-arginine; reduction of endothelin-1; relaxation of vascular smooth muscle cells; metabolic effects on perivascular adipocytes; endothelial regeneration. Mechanisms of hypertension-related organ damage protection: anti-inflammatory, antioxidant, and antithrombotic effects; reduction of arterial stiffness; experimental effects on LV hypertrophy and abnormal gene expression; effects on atherosclerotic plaque progression and stability [57].…”
Section: Omega-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Огляди measurement of velocity of the pulse-wave velocity (PWV) between two vascular points is an accepted method to assess arterial stiffness [57].…”
Section: проблеми ендокринної патології № 4 2018mentioning
confidence: 99%